About the relations between Management Accounting Systems, Intellectual Capital and Performance - Novas, Jorge (2012)
The present study is focused on the contribution of management accounting systems (MAS) in the development of intellectual capital (IC). Based on empirical evidence that supports the proposition that the value creation process is strongly associated to the level of IC, the study also examines the mediating effect of MAS on performance through their positive direct effect on IC. These relationships were consolidated into a model and empirically tested with data from 281 Portuguese firms using the Structural Equation Modeling (SEM). The findings show that six out of nine hypothesized relationships were supported by data with positive and significant causal links between MAS and the human and structural dimensions of IC. Results confirmed the conceptual validity of the circular model for the interactions among the three IC dimensions. Results also showed a positive and significant direct effect of structural capital on performance. Overall, the results confirmed the validity of the proposed model and contributed to the literature on the role of MAS in supporting the development of the IC